NASDAQ-inspired exchanges : a case study of Asia. - Fong, Hung Yee. (2008)
Asia is an assortment of different stories. The objective of this paper is to analyse the fundamental structure of an array of Asian second boards to determine the possibility of a Nasdaq in Asia.